2015
DOI: 10.1002/jtr.2054
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of City Branding Literature (1988–2014) as a Research Domain

Abstract: The purpose of this study is to systematically review the city branding literature, organize the subject matters and draw a map of the development and change in the city branding research domain. As a result, city branding literature is categorized under four thematic areas: (1) city branding concept, processes and measurement; (2) branding strategies; (3) social urbanism; and (4) branding culture and tourism. Most of the studies are research based. The qualitative methods are commonly used. There is a general… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
71
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(76 citation statements)
references
References 110 publications
(157 reference statements)
0
71
0
5
Order By: Relevance
“…Son estas organizaciones las que asignan los presupuestos, deciden y enfocan la transformación de las ciudades (Huertas 2014). El diálogo con las herramientas del marketing de ciudad, también se debe centrar mostrar la calidad de un lugar, su historia, el estilo y nivel de vida y la cultura como activos y ventajas competitivas (Oguztimur & Akturan, 2015) y debe estar en constante sinergia con factores de calidad reflejados en todos los aspectos que atañen el imaginario de ciudad, afectado en algunos casos por la imagen general de un país .…”
Section: Análisis De Los Resultadosunclassified
“…Son estas organizaciones las que asignan los presupuestos, deciden y enfocan la transformación de las ciudades (Huertas 2014). El diálogo con las herramientas del marketing de ciudad, también se debe centrar mostrar la calidad de un lugar, su historia, el estilo y nivel de vida y la cultura como activos y ventajas competitivas (Oguztimur & Akturan, 2015) y debe estar en constante sinergia con factores de calidad reflejados en todos los aspectos que atañen el imaginario de ciudad, afectado en algunos casos por la imagen general de un país .…”
Section: Análisis De Los Resultadosunclassified
“…This is mainly because of its interdisciplinary character, partly due to its derivation from marketing theories. In this ield, most scholars are human geographers and city planners, and they do not pay much atention to the marketing side of the concept [12].…”
Section: City Branding Argumentsmentioning
confidence: 99%
“…Nevertheless, cities are "highly complex brands" [10], serving varied goals and simultaneously targeting diferent groups and individuals, which make them "more diicult to control than conventional product brands" [11]. Besides, it is observed that most of the academic publications focus on what branding is not, rather than guiding to plan a city's real needs as empirical studies [12].…”
Section: Introductionmentioning
confidence: 99%
“…Given the free movement of capital and people in the 'age of cities' , it is essential for the sustainability of the city to maintain residents satisfied with the city. In the attempt for responding to the demands of competition and attract the specified target groups, there has been an increasing interest in city branding within academia and the public authorities during the last four decades (Oguztimur and Akturan 2016). Interest in city branding may be perceived as a component of a broader recognition framework that cities can benefit from implementing coherent strategies concerning the management of their resources and reputation (Dinnie 2010, p. 3).…”
Section: Introductionmentioning
confidence: 99%